French men's professional basketball under the economic shock of the covid-19 - Carin, Y.; Desquennes, C.; Jaworski, L.; Andreff, W. (Sport, Business and Management, 2022)
Purpose: The purpose of this paper is to analyse the economic effects of Covid-19 on French men's professional basketball club championships. Three research questions are raised: What are the characteristics of the economic model of French men's professional basketball? Has this economic model changed over the 2008/2009 to 2018/2019 period? What are the economic effects of the Covid-19 crisis on the finance of French men's professional basketball clubs?